The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/14644207221140246
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of particle reinforcement on friction stir weldment: A review

Abstract: Friction stir welding is a solid-state environment-friendly joining process with many advantages over all fusion welding processes. Many variants in friction stir welding are used for uplifting the process to its maximum possible extent. One such variant is particle reinforcement in the weldment, which is used for improving the mechanical properties by enhancing the metallurgical aspects in the weld region. Generally, micro- and nano-sized ceramic particles are used for reinforcing, which have a much higher me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 133 publications
0
1
0
Order By: Relevance
“…The contact area between the tool and workpiece governs the heat input, which is affected by tilt angle and plunger depth (Asadi et al , 2010). Some recent studies show that multiple passes led to homogeneous dispersion and grain refinement (Shivakumar and Rajamurugan, 2022; Gangil et al , 2018). Mazaheri et al revealed that the mean grain size was reduced from 10.2 to 2 µm of AZ31/ZrO 2 after four FSP passes (Mazaheri et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The contact area between the tool and workpiece governs the heat input, which is affected by tilt angle and plunger depth (Asadi et al , 2010). Some recent studies show that multiple passes led to homogeneous dispersion and grain refinement (Shivakumar and Rajamurugan, 2022; Gangil et al , 2018). Mazaheri et al revealed that the mean grain size was reduced from 10.2 to 2 µm of AZ31/ZrO 2 after four FSP passes (Mazaheri et al , 2020).…”
Section: Introductionmentioning
confidence: 99%